Reconstruction of Financing Agreement Based on the Principle of Profit and Loss in Sharia Banking - Trisadini Prasastinah Usanti; Abdul Shomad (Faculty of Law, Hasanuddin University, 2016)
The main purpose of this paper is to provide an analysis that with the reconstruction of the contract that is based on sharing profits and losses it will form a model contract that has Islamic values, maslahat and justice. In the practice of sharia banking in Indonesia, the financing agreement based on the principle of profit and loss sharing in form standard does not fully reflect the characteristic of the contract. Approach used is legislation approach, conceptual approach and contract approach. Legal materials consist of primary legal materials and secondary legal materials. The study is helpful in practice sharia banking, namely the model of financing contract based on the principle of profit and sharing. Standard contracts in sharia banking serve as a form of legal frame that can be reconstructed. The characteristics of the contract is based on the principle of profit and loss sharing which state is that no one is justified to get a profit without having to bear the business risk.